Peran Anonimitas dalam Mendorong Self-Disclosure pada Interaksi Sosial Komunitas Indo Hangout di Roblox - Taufikoh Rohadatul Aisyi; Mareta Puri Rahastine; Anggie Ayu Astria Latuperissa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the role of anonymity in fostering self-disclosure during social interactions among members of the Indo Hangout community on Roblox.The study employs a qualitative methodology with a phenomenological approach, aiming to explore members’ experiences in communicating through virtual identities. Five informants participated in this study; they were selected through purposive sampling based on their active participation in the community and their experiences with virtual self-disclosure. Data were collected through participant observation, semi-structured in-depth interviews, and documentation, and were then analyzed using the interactive model proposed by Miles and Huberman. The results indicate that anonymity acts as a catalyst for self-disclosure because it provides a sense of psychological safety, thereby reducing fears of judgment, stigma, and real-world social consequences. The process of self-disclosure occurs gradually, ranging from the exchange of general information to the sharing of more personal experiences and feelings. As closeness and trust among members increased, some individuals chose to reduce their level of anonymity by revealing their identities outside the platform. These findings confirm that anonymity not only serves as a shield for identity but also facilitates more relaxed communication, thereby strengthening closer social bonds within the virtual community.